Empower Generations: Longitudinal Study for National Capacities in Life Sciences and Healthcare - Althani, Asmaa Ali J. F.; Abu-El-Ruz, Rasha; Kurdi, Rana Mahmoud; Almeer, Naiema Hashem M. A.; Al-Ajli, Farooq Omar Maan; Al-Shafai, Mashael; Elgamal, Abdelrahman Mohamed; Latrous, Mariem Sirine; Hadwan, Tameem Ali Qaid; Abunada, Taghreed H. A.; Jamal, Zeina; Masoud, Ovelia Anan M. J.; et al. (Frontiers in Education, 2021)
The decreased number of adolescents who manifest genuine interest in the careers of life sciences and healthcare has been one of the recent concerns among the globe. Plethora of studies discussed the factors that influence the career choices for high school students such as; science educational pedagogy, gender, religion, environment, cognitive capabilities, and social perception of gender-based occupations. Reported in 2012, the majority of Qatari high school students have shown increased interests towards business, technological and administrative careers and decreased interests towards science careers; more specifically, life sciences and healthcare. Comprehensive national and institutional strategies have been embraced to close the arisen gap between the national supply and demands of Qatari healthcare and life sciences human capital. This five years longitudinal study has been performed in Qatar University based on retrospective anonymous data to examine the effectiveness of the Empower Generations (EG) educational framework in directing the interest of Adolescents towards the careers of life sciences & healthcare. The core concept of this study is extracurricular schematic educational framework that is designed for high school students. The educational framework involves four pillars; (1) life sciences and healthcare education that involves hands-on experiments in laboratory settings (2) field application for life sciences and healthcare occupations (3) science innovation competition (4) externship placement at various employers in research and healthcare sectors. A total of 324 high school female students were recruited with average of 64 students annually from various public and private high schools across Qatar. Comprehensive follow-up approach has been utilized in this study to tackle the final career choices of the participants. The findings were analyzed statistically through Statistical Package for the Social Sciences Software (SPSS). The descriptive statistics showed that 79.8% of the participated students reported that Empower Generations (EG) has changed their interest. 97.5% recommended this program to other students. 60.4% said that they will consider healthcare related careers. 28.3% actually enrolled healthcare related university majors and 9% enrolled life sciences related majors. On the other side, 28.3% did not enroll in life sciences or healthcare related majors and 29.9% are still pursuing their high school final years.